Study and Analysis of Various Image Enhancement Method using MATLAB - Kushwaha, Sumit; Kumar Singh, Rabindra (International Journal of Computer Sciences and Engineering, 2015)
The main objective of image enhancement is to process the input image so that the processed image will look much better. Image enhancement refers to accentuation, or sharpening of image features such as edges, boundaries, or contrast to make a graphic display more useful for display and analysis. It plays a vital role in every field. This paper covers two parts: first part is based to the study of various types of images and image enhancement and second part is based on analysis of various basic intensity transformation functions in image processing. All these analysis is performed in MATLAB software. We get various results in term of output images and their histograms respectively. Here we see that each transformation function is suitable for some particular applications, not for all. So, According to application requirement, we choose a particular transformation function for image enhancement.